2023
DOI: 10.3390/machines11010114
|View full text |Cite
|
Sign up to set email alerts
|

Fault Prediction of On-Board Train Control Equipment Using a CGAN-Enhanced XGBoost Method with Unbalanced Samples

Abstract: On-board train control equipment is an important component of the Train Control System (TCS) of railway trains. In order to guarantee the safe and efficient operation of the railway system, Predictive Maintenance (PdM) is significantly required. The operation data of the on-board equipment allow us to build fault prediction models using a data-driven approach. However, the problem of unbalanced fault samples makes it difficult to achieve the expected modeling performance. In this paper, a Conditional Generativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Many existing PdM models are based on machine learning or deep learning methods [21], which generally require a large amount of failure data for training aimed at estimating the RUL or predicting impending anomalies [22]. Data collection is hindered by a severe imbalance between normal data (abundant) and abnormal data (scarce), which can render conventional machine learning or deep learning methods ineffective [23]. Several researchers have proposed the pre-training of deep learning models or the use of transfer learning to reduce data size requirements [24]; however, engineers have found that the inference process lacks interpretability.…”
Section: A Backgroundmentioning
confidence: 99%
“…Many existing PdM models are based on machine learning or deep learning methods [21], which generally require a large amount of failure data for training aimed at estimating the RUL or predicting impending anomalies [22]. Data collection is hindered by a severe imbalance between normal data (abundant) and abnormal data (scarce), which can render conventional machine learning or deep learning methods ineffective [23]. Several researchers have proposed the pre-training of deep learning models or the use of transfer learning to reduce data size requirements [24]; however, engineers have found that the inference process lacks interpretability.…”
Section: A Backgroundmentioning
confidence: 99%
“…This combination allows XGBoost to achieve excellent model performance and high-speed processing. Liu et al (2023) utilized XGBoost to enhance the predicted outcomes developed from conventional machine learning algorithms and resulted in an increased F1-score of 6.13%. On imbalanced dataset such as personal credit evaluation, XGBoost performed better than the other tree-based models and logistic regression (Li et al, 2020).…”
mentioning
confidence: 99%